Drug reaction with eosinophilia and systemic symptoms associated with carbamazepine (DRESS syndrome) - case report and literature review - Kamila Ociepa; Anna Woźniacka; Agnieszka Żebrowska (Termedia Publishing House, 2016)
Introduction. Drug reaction with eosinophilia and systemic symptoms (DRESS) is a serious, potentially life-threatening syndrome with skin lesions, internal organ involvement and eosinophilia. Objective . To present the case of a 35-year-old woman with DRESS syndrome after 6 weeks of treatment with the anticonvulsant drug carbamazepine. Case report . A 35-year-old woman, suffering from depression, was admitted to hospital after a single exposure to artificial ultraviolet radiation during carbamazepine therapy. Generalized maculopapular eruptions and laboratory blood test abnormalities were recognized. After withdrawal of the causative drug and treatment with corticosteroids and antihistaminic preparations, the skin lesions disappeared and the values of laboratory blood tests improved. Conclusions . Due to the high rate of mortality in DRESS, a quick diagnosis is of crucial value. Most important is detailed history taking, immediate cessation of the causative drug, and in severe cases therapy with systemic corticosteroids. Proper diagnosis reduces the rate of fatal outcome of the disease, which is estimated at 10-38%.